2018
DOI: 10.1108/sajbs-11-2016-0091
|View full text |Cite
|
Sign up to set email alerts
|

Decoding willingness of Indian consumers to pay a premium on green products

Abstract: Purpose The purpose of this paper is to identify the relevant antecedents of willingness of Indian consumers to pay a premium for green products and empirically validate the relationship between these antecedents and willingness to pay (WTP). Design/methodology/approach Data were generated from 515 students enroled in various educational institutions approved by the All India Council for Technical Education and located in New Delhi and National Capital Region region of India. A combination of researcher-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 77 publications
5
35
0
1
Order By: Relevance
“…The last hypothesis was validated ( H4 ; β = 0.218, t = 4.456 , p = 0.00) and suggested a positive impact of WTP on PIRC. This confirmed the results of the recent studies (Prakash and Pathak, 2017; Kirmani and Khan, 2018) which found that Indian consumers are willing to pay for products with low environmental impact. Therefore, it can be concluded that WTP positively influences PIRC.…”
Section: Discussionsupporting
confidence: 91%
“…The last hypothesis was validated ( H4 ; β = 0.218, t = 4.456 , p = 0.00) and suggested a positive impact of WTP on PIRC. This confirmed the results of the recent studies (Prakash and Pathak, 2017; Kirmani and Khan, 2018) which found that Indian consumers are willing to pay for products with low environmental impact. Therefore, it can be concluded that WTP positively influences PIRC.…”
Section: Discussionsupporting
confidence: 91%
“…Hence, environmental concern is considered as the adjusting variable in this study, in order to discuss the influence of environmental concern on innovation resistance. Previous studies have employed the contingent valuation method (CVM) to assess the benefits of green products [27][28][29]. Moreover, Costa et al [30] and Arega and Tadesse [31] suggested that consumers are likely to pay more for green products, with their willingness to consume green products depending on whether the willingness-to-pay (WTP) exceeds the price of the green products.…”
Section: Introductionmentioning
confidence: 99%
“…(2015) observed that willingness differs across consumers and creates a gap between intention and actual behaviour. In addition to the organizational image, environmental knowledge and awareness, positive attitude and satisfaction from past purchases are identified as leading antecedents to consumers’ intention for future purchases (Kirmani & Khan, 2018). Consumers independently evaluate their perception and satisfaction (Nguyen, Nguyen, & Hoang, 2019; Nguyen, Nguyen, Nguyen, et al., 2019; Wu & Cheng, 2019), but instrumental values (Kautish & Sharma, 2018) also influence purchase intention.…”
Section: Results From Literature Reviewmentioning
confidence: 99%